Biomineralization Efficiency of Halophilic Bacteria and Their Role in Building Structures - Divyanshi (My University, 2019)
Halophilic microbes have always been a hotspot for researchers due to their ability to survive the extreme conditions, that most of other organisms are unable to endure. Also, during a past few decades, various microbes have been studied for their ability to produce biominerals. Present study focuses on isolation of a novel strain from hypersaline habitat, i.e., Sambhar Lake, Jaipur, Rajasthan. The growth of isolated strain (SL-1) at varying alkalinity stress was monitored along with its proficiency to heal concrete structures in terms of mechanical strength, water and ionic ingress, crystal morphology and amount of CaCO3 precipitated. It was observed that SL-1 grew best in growth medium with 3.5% NaCl concentration (pH 10) and its inculcation into concrete cubes resulted in an increase of 16% of strength along with significant reduction in water absorption. Present study suggests that CaCO3 precipitation by halophilic strain can nullify the deterring effect of ionic permeation through salts in saline environment in concrete structures.
Keywords: microbial induced calcium precipitation; biomineralization; Halophilc bacteria; Bacillus paramycoides; concrete; salt stress